Prognostic value of lipid metabolism‐related genes in head and neck squamous cell carcinoma - Ying Xiong; Yu Si; Yisi Feng; Shipei Zhuo; Bozhen Cui; Zhigang Zhang (Immunity, Inflammation and Disease)
Abstract Background Altered lipid metabolism is involved in the development of many tumors. However, the role of dissimilar lipid metabolism in head and neck squamous cell carcinoma (HNSCC) is not fully established. Aims Here, we sought to determine the prognostic value of lipid metabolism‐related genes in HNSCC. Methods RNA‐seq data and clinical features of 545 HNSCC cases were obtained from The Cancer Genome Atlas database. A regulatory network of transcription factors‐lipid metabolism genes and a risk prognostic model of lipid metabolism‐related genes was developed using bioinformatics and Cox regression modeling. We used tumor immune estimation resource to analyze immune cell infiltration in patients with HNSCC based on the prognostic index (PI) of lipid metabolism‐related genes. Results A total of 136 differentially expressed lipid metabolism genes were identified. Of these, 23 are related to prognosis. In addition to predicting HNSCC prognosis, 11 lipid metabolism‐related genes (ARSI, CYP27B1, CYP2D6, DGKG, DHCR7, LPIN1, PHYH, PIP5K1B, PLA2G2D, RDH16, and TRIB3) also affect HNSCC clinical features (stage, gender, and pathological stage). The PI of lipid metabolism‐related genes embodied the state of HNSCC tumor immune microenvironment.